Factors in Managing Organizational Effectiveness: The Case of Iran’s Economy - Mehdi, Safdari (Information Management and Business Review, 2011)
Today, the most important element of economic is management and here, looking scholars management is the process in efficient use of resources therefore being numerous human and material resources are useable. Money and capital are important factor in the economy but when this factor is satisfactory that be managed optimal way also human and software resources are important factor in the economy but when these factors are useful that be managed optimal way. The aim of the study is to determine the relationship between leadership styles of managers with organizational commitment that staff are under their supervision and productivity in the Iran’s economy in a sample and also investigated some demographic characteristics associated with leadership style variables of managers and staff organizational commitment. Stationary or non stationary variables were analyzed by Augmented Dickey Fuller (ADF) and in order to analyze the data, is used analysis of variance and regression analysis.